A SURVIVAL OF PATIENTS IN MAINTENCE HEMODIALYSIS DEPENDING ON EXPRESSED ANAEMIA AND CHARACTER OF DEFEAT OF KIDNEY - V. Savchuk (Ukrainian Journal of Nephrology and Dialysis, 2017)
The aim of the present research was to study the survival of hemodialysis (HD) patients depending on of anemia and character of kidney damage, «hemoglobin variability”Materials and methods: We have conducted a retrospective study of 183 hemodialysis patients who were treated from 2009. to 2012. The starting point of observation was defined the first hemodialysis session. The patients were divided in accordance of hemoglobin (Hb) levels for 4 groups: the level of Hb <70 g/l (n=32) – group I, Hb 70–89 g/l (n=68) - group II, Hb 90-110 g/l (n=65) – group III, Hb≥110g/l (n=28) - IV group.Results. The cumulative survival of patients was 55% at the moment of the end of the study. The cumulative proportion surviving of patients with diabetes mellitus was significantly lower compared to non-diabetic patients – 18% and 57%, respectively.The survival of patients I & II groups was significantly lower than the patients of  groups III & IV: 83.64% and 63.75% versus 31.7% and 29.28%, respectively (criteria Geha-Wilcoxon, Cox-Mantel test, Wilcoxon-Peto, F-criterion Cox log-rank test).The survival of patients with "stable hemoglobin" was significantly higher than in patients with "low of hemoglobin variability " and "high of hemoglobin variability"(р<0,005).Conclusions. Hb level and its variability had a significant effect on the survival of patients who are treated with hemodialysis. The survival of hemodialysis patients with diabetes mellitus was significantly lower than in non-diabetic kidney failure.